Persepsi Pelajar Terhadap Hubungan antara Sikap dan Amalan Guru dalam Kelas dengan Masalah Devian (Pelanggaran Disiplin) Para pelajar Sekolah-Sekolah Menengah di Daerah Jeli, Kelantan - Saleh @ Bustaman, Hamat (2003)
A case study has been carried out the relationship between teachers' attitude and habit in the classroom towards indisciplinary problems among secondary students in the district of Jeli, Kelantan. Other aspects are also included in this study such as related factors that might contribute other then teachers' attitude for example influence from the inside and outside school environment and existing factors from the student itself. This study involved 206 respondent of form four and five. Research question have been administered to acquire data, A and B. Section A consisted data about the background of the respondents and section B, data regarding the perception of students about factors that might contribute toward student's indisciplinary action. Data obtained have been analyzed through the descriptive statistic to show the frequency, the percentage, mean and standard deviation. Inferential statistic is also used to conducting the T-test and one tail Anova (Analysis of Variance). As a result, it is finding, that the most dominant factor that influences the student's indisciplinary action is factors involved from outside the school. Other factors, such as teachers' habit in classroom, school environment and student's attitude are less influential.